Unilateral hearing during development: hemispheric specificity in plastic reorganizations - Kral, Andrej; Heid, Silvia; Hubka, Peter; Tillein, Jochen (Frontiers in Systems Neuroscience, 2013)
The present study investigates the hemispheric contributions of neuronal reorganization following early single-sided hearing (unilateral deafness). The experiments were performed on ten cats from our colony of deaf white cats. Two were identified in early hearing screening as unilaterally congenitally deaf. The remaining eight were bilaterally congenitally deaf, unilaterally implanted at different ages with a cochlear implant. Implanted animals were chronically stimulated using a single-channel portable signal processor for two to five months. Microelectrode recordings were performed at the primary auditory cortex under stimulation at the hearing and deaf ear with bilateral cochlear implants. Local field potentials (LFPs) were compared at the cortex ipsilateral and contralateral to the hearing ear. The focus of the study was on the morphology and the onset latency of the LFPs. The data revealed that effects of hearing experience were more pronounced when stimulating the hearing ear. With respect to morphology of LFPs, pronounced hemisphere-specific effects were observed. Morphology of amplitude-normalized LFPs for stimulation of the deaf and the hearing ear was similar for responses recorded at the same hemisphere. However, when comparisons were performed between the hemispheres, the morphology was more dissimilar even though the same ear was stimulated. This demonstrates hemispheric specificity of some cortical adaptations irrespective of the ear stimulated. The results suggest a specific adaptation process at the hemisphere ipsilateral to the hearing ear, involving specific (down-regulated inhibitory) mechanisms not found in the contralateral hemisphere. Finally, onset latencies revealed that the sensitive period for the cortex ipsilateral to the hearing ear is shorter than that for the contralateral cortex. Unilateral hearing experience leads to a functionally-asymmetric brain with different neuronal reorganizations and different sensitive periods involved.